2019
DOI: 10.1002/lom3.10311
|View full text |Cite
|
Sign up to set email alerts
|

Data trend shifts induced by method of concentration for trace metals in seawater: Automated online preconcentration vs. borohydride reductive coprecipitation of nearshore seawater samples for analysis of Ni, Cu, Zn, Cd, and Pb via ICP‐MS

Abstract: This research compares performance, reproducibility, and detection limits of ambient seawater analysis for trace metals using both borohydride reductive coprecipitation and an automated chelation column (seaFAST™ 2) preconcentration for matrix interferent elimination on total and dissolved grab samples in nearshore to marine waters, over a broad concentration range, prior to inductively coupled plasma mass spectrometry (ICP‐MS) injection. A move to an online preconcentration method both minimizes sample prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For analysis of dissolved metals in seawater, samples were first prepared using a total recoverable metal digestion and then preconcentrated via a seaFast® chelation step (Strivens et al 2019a). For labile metals, Chelex resins were eluted in 1 mL concentrated Optima™ grade nitric acid (Fisher Scientific) for 24 h, at room temperature, then diluted to 15 times.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of dissolved metals in seawater, samples were first prepared using a total recoverable metal digestion and then preconcentrated via a seaFast® chelation step (Strivens et al 2019a). For labile metals, Chelex resins were eluted in 1 mL concentrated Optima™ grade nitric acid (Fisher Scientific) for 24 h, at room temperature, then diluted to 15 times.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, a commercially available automated module, the seaFAST system, simplifies and streamlines the pre-processing treatment of seawater samples. Several studies have shown the potential of using the seaFAST pre-treatment system before quantifying trace metals [9][10][11][12][13], rare earth elements [14,15], and their isotopic composition [16]. Once preconcentrated, the advanced, high-resolution mass spectrometers, e.g., sector field (SF-ICPMS; [9]) and triple quadrupole (QQQ-ICPMS; [10]) have been commonly used for quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Once preconcentrated, the advanced, high-resolution mass spectrometers, e.g., sector field (SF-ICPMS; [9]) and triple quadrupole (QQQ-ICPMS; [10]) have been commonly used for quantification. In some studies, a single quadrupole ICPMS was also applied for the determination of trace metals [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…seaFAST (Elemental Scientific), provided an approach for pH adjustment by diluting the sample with an ammonium acetate buffer. [40][41][42][43][44][45] Due to the limited naturalization capability of ammonium acetate buffer, the samples after pH adjustment usually had high concentrations of ammonium ions and acetate ions. They may compete with the cations of trace elements and the functional groups of the chelating resin, respectively, during the SPE operations.…”
Section: Introductionmentioning
confidence: 99%
“…Apparent lower recoveries for some elements reported might be attributed to such cations and anions competition. 41,44,45 As an alternative approach for precise pH adjustment in SPE operations with chelating resin, the authors had developed an automatic pH adjustment instrument and applied to the the controlling computer sent open/close command to the I/O board (6) and then to the electro-magnetic valve (8). The open/close operation of the electro-magnetic valve (8) controlled the supply of ammonia solution (9) through the nebulizer (10) to the sample solution (2), where the addition of ammonia solution (2) through the nebulizer (10) was driven by the air (11) with a flow rate of approximately 1.0 L min -1 and resulting in an uptake rate of ammonia solution at 0.5 mL min -1 , where an in-line filter was equipped to prevent contamination from the atmosphere.…”
Section: Introductionmentioning
confidence: 99%